The issue of incorporating the concept of good faith in Australian contract law: Implication or construction - Abdullah, N.; Kari, F.; Ismail Nawang, N. (2015)
Good faith is arguably the most controversial concept in Australian contract law despite no high court decision deciding its application. The case of Renard Constructions (ME) Ply Ltd v Minister for Public Works (1992) 26 NSWLR 234 introduced the concept of good faith for the first time by way of obiter comment by Priestley J. In this case, it was argued that good faith is implied by 'Implication'. The objective of this paper is to analyse the issue of incorporating the concept of good faith in Australian contract law either by way of 'Implication' or 'Construction'. There are two types of implication of a term; 'implied by fact' and 'Implied by law'. This is a library-based research paper and uses a qualitative approach to compare both approaches in implying the concept of good faith. The paper concludes that good faith is easier to identify from the term 'implied by law' which is based on the legal incident of a particular class of contract.